2006
DOI: 10.1051/forest:2006035
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of wood extracts and colour stability of woods

Abstract: -Industrial wood extracts were selected and other extracts were prepared in the laboratory from some chosen wood species. Antioxidant capacities of extracts were measured by three methods: the oxygen uptake method, the kinetic DPPH method, and the equilibrium DPPH method. There is a fair correlation between the three methods. Total phenol contents of the extracts and colour stability of woods were measured. For the same phenol content, extracts containing condensed tannins are more antioxidant than those conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…The maximum yield obtained in this study was low and similar to other reported for Pinus radiata bark (2.0 %); although, with different operating conditions (extraction time 24 h and, solvent Met OH/H 2 O (7:3 % v/v)) (Diouf et al 2006). Using more aggressive conditions (NaOH/H 2 O 1%, 100ºC), Ku and Mun (2007) increased ten times the yield.…”
Section: Yield Extraction Of Bark From Young and Old Treessupporting
confidence: 60%
See 1 more Smart Citation
“…The maximum yield obtained in this study was low and similar to other reported for Pinus radiata bark (2.0 %); although, with different operating conditions (extraction time 24 h and, solvent Met OH/H 2 O (7:3 % v/v)) (Diouf et al 2006). Using more aggressive conditions (NaOH/H 2 O 1%, 100ºC), Ku and Mun (2007) increased ten times the yield.…”
Section: Yield Extraction Of Bark From Young and Old Treessupporting
confidence: 60%
“…Considering the differences in the extraction method, quantification methodology and data reports, it is difficult to compare our results with values obtained for Pinus radiata bark extracts in other studies. Still, total phenols content was found to be higher than the values obtained for other Pinus radiata analyzed with the same analytical method (Diouf et al 2006, Raghavendra et al 2007). …”
Section: Characterization Of the Extractsmentioning
confidence: 66%
“…Except for lime wood, the lowest extraction yields were obtained for the water extractions and the highest for the extractions carried out with an aqueous solution of 1 % sodium hydroxide and 1 % sodium sulphite. Significantly lower extraction yields (2-14.7 %) were obtained for wood and bark extracted with methanol/water 70:30 (v/v) (Diouf et al 2006), and it is noteworthy that the lowest value corresponded to pine bark. Although a high extraction yield is important in terms of process economic viability, it must be accompanied by extracts with high values of those properties related to prevent wood photodegradation, as is the case for extract antioxidant activity which was evaluated by different methods.…”
Section: Resultsmentioning
confidence: 98%
“…Using ESR spectroscopy it was demonstrated that wood radicals induced by UV light were inhibited by Acacia confusa heartwood extracts and consequently wood photodegradation was retarded (Chang et al 2014). Diouf et al (2006) found that wood species with low antioxidant capacity happened to be less colour durable, whereas those with high antioxidant capacity were more light resistant. Additionally, color stability was conferred to non durable woods if impregnated with extracts of durable species.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Jerez et al (2006Jerez et al ( , 2007b, Ku et al (2007) and Diouf et al (2006) used 0.16 L reactors, 0.25 L extractors and 22 cm 3 cells, respectively;…”
Section: Introductionmentioning
confidence: 99%